Briquettes production as teaching aids physics for improving science process skills. Issue 3 (February 2019) - Haryadi, R; Vita, M; Utami, I S; Ihsanudin, I; Setiani, Y; Suherman, A
Abstract: The aim of this research is production briquettes as teaching aids in order to improve students' science process skill. Research design used in this study was using experimental methods. One of the learning methods that can be used to equip student's science process skill is the experimental method. In this study, students utilize agricultural waste and plantations around the school. Then they make the briquettes from the waste. This research used waste rice husk waste, durian leather and coconut fiber. After that, the results of briquettes will be assessed as the feasibility of teaching aids. The results of students' affective and psychomotor ratings show excellent results. Among them are: classical affective average score for group 1 is 82.80; group 2 is 87.20; and group 3 is 85.20. While the classical average psychomotor score for group 1 is 82.80; group 2 is 86.20; and group 3 is 84.20.